HDAC8 regulates a stress response pathway in melanoma to mediate escape from BRAF inhibitor therapy - Emmons, Michael F. (Cancer Res, 2019)
Melanoma cells have the ability to switch to a dedifferentiated, invasive phenotype in response to multiple stimuli. Here we show that exposure of melanomas to multiple stresses including BRAF-MEK inhibitor therapy, hypoxia, and UV irradiation leads to an increase in histone deacetylase 8 (HDAC8) activity and the adoption of a drug-resistant phenotype. Mass spectrometry-based phosphoproteomics implicated HDAC8 in the regulation of MAPK and AP-1 signaling. Introduction of HDAC8 into drug-naïve melanoma cells conveyed resistance both in vitro and in vivo. HDAC8-mediated BRAF inhibitor resistance was mediated via receptor tyrosine kinase (RTK) activation, leading to MAPK signaling. Although HDACs function at the histone level, they also regulate non-histone substrates, and introduction of HDAC8 decreased the acetylation of c-Jun, increasing its transcriptional activity and enriching for an AP-1 gene signature. Mutation of the putative c-Jun acetylation site at lysine 273 increased transcriptional activation of c-Jun in melanoma cells and conveyed resistance to BRAF inhibition. In vivo xenograft studies confirmed the key role of HDAC8 in therapeutic adaptation, with both non-selective and HDAC8-specific inhibitors enhancing the durability of BRAF inhibitor therapy. Our studies demonstrate that HDAC8-specific inhibitors limit the adaptation of melanoma cells to multiple stresses including BRAF-MEK inhibition.